Introgression Analysis and Morphological Characterization of an Arachis hypogaea × A. diogoi Interspecific Hybrid Derived Population. Issue 2 (1st March 2019) - Hancock, Wesley G.; Tallury, Shyam P.; Isleib, Thomas G.; Chu, Ye; Ozias-Akins, Peggy; Stalker, H. Thomas
Abstract : Cultivated peanut ( Arachis hypogaea L.) is an economically important crop grown around the world. Compared with the entire Arachis genus, cultivated peanut germplasm has low levels of genetic diversity for several economically important traits, resulting in the need for alternative sources of favorable alleles. Wild diploid species of Arachis are a source of such alleles to improve cultivated peanut for many economically important traits. An A. hypogaea × A. diogoi Hoehne introgression population was produced via the triploid–hexaploid method; the fourth generation after tetraploidy was used to initiate this study. The introgression lines were genotyped using a single nucleotide polymorphism (SNP) marker array to estimate the percentage of A. diogoi chromatin introgression. Morphologically, the introgression lines varied for an array of measured traits, with the majority being intermediate to the two parents. The average amount of A. diogoi genome introgressed was 8.12% across the tetraploid genome and ranged from 3.00 to 18.14% on individual chromosomes. The average A. diogoi introgression across all lines was 7.70% and ranged from 0.17 to 51.12%. Principal component analysis of morphological data and SNP markers revealed similarities and groupings of introgression lines. This introgression population demonstrates the potential of using wild diploid Arachis species for peanut improvement and has great potential for use in cultivated peanut breeding programs.